1996
DOI: 10.1007/bf01409983
|View full text |Cite
|
Sign up to set email alerts
|

The relation between cartilage damage and osteophyte size in a murine model for osteoarthritis in the knee

Abstract: The aim of this study was to investigate the relationship between location and size of osteophytes and cartilage loss in an instability-induced experimental model for osteoarthritis. Osteoarthritis was induced in murine knee joints by injection of highly purified bacterial collagenase, causing joint instability. The size of the osteophytes and the cartilage loss were measured at different locations in the joint using image analysis on histological sections of total kees. Cartilage damage did not occur without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…11 In a murine model of OA a good correlation has been reported between osteophyte size and cartilage damage. 6 In our study a similarly strong association was observed between osteophyte size and local cartilage narrowing, especially in the medial TFJ and lateral PFJ. However, osteophyte size in the lateral TFJ showed a stronger association with narrowing in the medial TFJ and lateral PFJ than in its own compartment, and osteophyte size in the medial PFJ showed no correlation with local narrowing but an association with narrowing in the medial TFJ.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…11 In a murine model of OA a good correlation has been reported between osteophyte size and cartilage damage. 6 In our study a similarly strong association was observed between osteophyte size and local cartilage narrowing, especially in the medial TFJ and lateral PFJ. However, osteophyte size in the lateral TFJ showed a stronger association with narrowing in the medial TFJ and lateral PFJ than in its own compartment, and osteophyte size in the medial PFJ showed no correlation with local narrowing but an association with narrowing in the medial TFJ.…”
Section: Discussionsupporting
confidence: 78%
“…van Osch et al speculated that cartilage damage and osteophyte formation are not directly linked but that both are induced by the same factor and develop independently of each other. 6 Such independent development may have been observed in the lateral PFJ and medial TFJ, where osteophyte size associates more with lateral patella subluxation and femorotibial angle, respectively, than with local narrowing.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We also found that the correlation of osteophyte formation to the degree of cartilage loss is significant but weak (correlation coefficient ranging from 0.22 to 0.41, P less than 0.01). Previous studies found significant association between the degree of osteophyte formation and cartilage lesion [2,17]. Boegard et al [2] found strong association between radiographically diagnosed osteophytes and cartilage defects detected by MRI.…”
Section: Discussionmentioning
confidence: 98%
“…injection of collagenase is an established model of OA that has been predominantly used to study the mechanisms underlying structural joint damage [15-17]. Histopathological alterations of the knee joint very similar to those observed in human OA have been described for this model, particularly in mice [18,19] and rabbits [20], as well as in the lumbar facet joint of rats [21].…”
Section: Introductionmentioning
confidence: 99%